The influence of physical environment, perceived emotional value, guest satisfaction and price fairness on Airbnb revisit intention in Malaysia / Nor Maizana Mat Nawi - Mat Nawi, Nor Maizana (2024)
The hospitality industry has been making a remarkable contribution to the growth of economies in several countries, and the rapid growth of hospitality businesses has made them a serious competitor in this industry. Airbnb, for instance, has become one of the most successful pioneers of the sharing economy, transforming the travel industry around the world. Airbnb accommodations in Malaysia are increasingly gaining popularity; nevertheless, the lack of the physical environment in Airbnb listing may result in guests not having a clear idea of the physical environment and this can lead to an unclear context of how the physical environment influences Airbnb guests. Hence, it was crucial to examine how physical environment influence revisit intention. Based on the previous literature, there was inconsistency of findings the influence of physical environment to predict guest revisit intention. Limited study on physical environment have used Stimulus-Organism-Response (SOR) theory as the study framework to predict guest revisit intention in Airbnb context. This study employed a quantitative research methodology using a survey questionnaire involving guests with Airbnb experiences was carried out with a total of 238 respondents. Data collected were analyzed to yield descriptive statistics and PLS-SEM was used to test the hypotheses of the study and evaluate the model. Based on the descriptive analysis results, most of the respondents believed that the physical environment experience might alter guests’ choice processes and create a positive mood for future behaviour. This study provide theoretical implications as the results of the study can enrich the current knowledge of how physical environment as stimulus in situations where perceived emotional value and satisfaction as emotions to predict guest revisit intention as final response in Malaysian Airbnb context. In addition, the current finding presents methodological implication as physical environment was addressed as Type II reflective-formative (composite) second-order constructs and contribute to the body of knowledge on physical environment field by examining price fairness as the moderating variable and perceived emotional value and guest satisfaction as the mediator variable. The novelty of the current study proved that perceived emotional value and guest satisfaction in the Stimulus-Organism-Response (SOR) model play a mediating role in determining guest revisit intention in Malaysian Airbnb. Overall, the findings of this study can help the hosts of Airbnb accommodations and other industry players understand the physical environment dimensions better, including the value that stimulates guest experience and emotions. As a result, guests will have a pleasant stay with Airbnb, which may influence their satisfaction and revisit intention especially in a Malaysian context.